Keanekaragaman Fitoplankton di Padang Lamun Kawasan Pesisir Mandalika Kabupaten Lombok Tengah - Rizkia Apriani; Sri Puji Astuti; Dining Aidil Candri; Hilman Ahyadi; Suripto Suripto; Sari Novida (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Phytoplankton is a source of food for zooplankton, fish larvae, and other organisms that live in seagrass beds. The purpose of this study was to determine the diversity of phytoplankton in seagrass beds in the coastal area of Mandalika, Central Lombok Regency. The location of water sample data collection was determined by purposive sampling by considering the percentage of seagrass cover. The sampling locations included 3 water locations, namely seagrass beds on the coast of Kuta, seagrass beds on the coast of Tanjung Ann, and seagrass beds on the coast of Gerupuk Bay. The research was conducted for three months from July to September 2021. The results of the study in the Mandalika coastal seagrass beds found 6 classes of phytoplankton, 26 orders, 30 families, 42 genera, and 46 phytoplankton species. Twenty one species of phytoplankton are from the Class Bacillariophyceae, 9 species from the Class Dinophyceae, 7 species from the Class Chlorophyceae, 5 species from the Class Cyanophyceae, 3 species from the Class Chrysophyceae, and 1 species from the Class Rhodophyceae. The abundance of phytoplankton at the three sampling locations ranged from 285-445 ind/L. The Phytoplankton Diversity Index in the three locations ranged from 1.35 to 2.75, which means communities with moderate diversity and dominance index ranged from 0.20-2.33.